A Review of Challenges of Block Chain with COVID-19: A Review Paper - Alarjani, Maitha; Alhaider, Malak (European Journal of Health Sciences, 2023)
COV-19 has a negative impact on human life and several sectors, particularly the health, financial, and tourism sectors. Such circumstances led to the concept of new forms of life that people have had to adapt to lessen the spread of disease by taking preventive precautions as recommended by governments and international organizations such as the WHO. As a result, authorities and technical associations must take advantage of the current technological advancements to overcome the challenges posed by these circumstances. Blockchain (BC) technology has been identified as a platform for cryptocurrency globally. However, BC technology has the wonderful ability to facilitate the transition from a centralized, low-trust transaction ledger to a decentralized, high-trust ledger held by multiple verifying nodes. Due to its distributed nature and protection, BC can be used in various fields other than cryptocurrency. BC plays an important role in improving and maintaining the privacy, security, and integrity of data. This paper aims to discuss the background of the BC technology and its applications in combating the COV-19 crisis. Also investigated existing BC methods in specific applications and analyze the effectiveness of their outcomes. Furthermore, the most recent BC-based research proposals for combating the COV-19 pandemic are reviewed.